2020
DOI: 10.1016/j.memsci.2019.117392
|View full text |Cite
|
Sign up to set email alerts
|

Improved reverse osmosis thin film composite biomimetic membranes by incorporation of polymersomes

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…PP+ consisted of a 1.12 mg/mL mixture of poly(2-methyl-2-oxazoline)-block-poly(dimethylsiloxane) (PMOXA-PDMS) diblock copolymer, poly(2-methyl-2-oxazoline)-block-poly(dimethylsiloxane)-block-poly(2-methyl-2-oxazoline) (PMOXA-PDMS-PMOXA) triblock copolymer, and bis(3-aminopropyl)-terminated poly(dimethylsiloxane) (A-PDMS) in phosphate-buffered saline (PBS) with 0.05% lauryldimethylamine N-oxide (LDAO), 0.5% Kolliphor® HS 15 (KHS), and 5 mg/L aquaporin Z protein. They were prepared via bulk hydration self-assembly, according to procedures described by M. Spulber et al [34] and in a study by Górecki et al [22] The average particle size of PP+ was reported to be 150 ± 1 nm with total particle concentration of 3.26 × 10 11 ± 7.08 × 10 9 particles/mL, and a neutral to slightly positive ζ-potential (+0.9 mV) due to the A-PDMS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PP+ consisted of a 1.12 mg/mL mixture of poly(2-methyl-2-oxazoline)-block-poly(dimethylsiloxane) (PMOXA-PDMS) diblock copolymer, poly(2-methyl-2-oxazoline)-block-poly(dimethylsiloxane)-block-poly(2-methyl-2-oxazoline) (PMOXA-PDMS-PMOXA) triblock copolymer, and bis(3-aminopropyl)-terminated poly(dimethylsiloxane) (A-PDMS) in phosphate-buffered saline (PBS) with 0.05% lauryldimethylamine N-oxide (LDAO), 0.5% Kolliphor® HS 15 (KHS), and 5 mg/L aquaporin Z protein. They were prepared via bulk hydration self-assembly, according to procedures described by M. Spulber et al [34] and in a study by Górecki et al [22] The average particle size of PP+ was reported to be 150 ± 1 nm with total particle concentration of 3.26 × 10 11 ± 7.08 × 10 9 particles/mL, and a neutral to slightly positive ζ-potential (+0.9 mV) due to the A-PDMS.…”
Section: Methodsmentioning
confidence: 99%
“…Obtained PP+ were filtered by a 0.4-µm Whatman filter prior to use. To check the PP+ solution quality, the filtered solution was measured by dynamic light scattering (DLS) Zetasizer Nano Zs (Malvern, United Kingdom); if a >85% intensity peak at 150-250 nm was observed, then the solution was recognized as good quality [22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These trends bring about RO membranes containing a wide variety of nanoparticles, including zeolites (silicate and NaA, NaX, NaY—i.e., different silica–alumina ratio), carbon materials (including carbon nanotubes and graphene oxide), silica, metal oxides (titanium dioxide), metal nanoparticles, and there has even been an attempt to introduce novel organic–inorganic hybrid materials (ZIF-8) into aromatic polyamide layers of RO membranes [ 48 ]. Special newly developed thin film composite biomimetic membranes greatly increase the effectivity of water transport in RO membranes, and increase desalination effectivity [ 49 ]. Additionally, according to the huge desalting RO plants, huge “kits” or “sets of blocks” of modules are being developed ( Figure 15 ).…”
Section: Optional Novel Materialsmentioning
confidence: 99%